Prostatic abscess as a presenting feature of paradoxical TB-IRIS - Achappa, Basavaprabhu; Shenoy, Archana; Ching Hsia, Mak; Yadlapati, Sujani; Madi, Deepak; Mahalingam, Soundarya (Asian Journal of Medical Sciences, 2014)
Paradoxical tuberculosis – immune reconstitution syndrome (pTB-IRIS) is a well-recognized cause of clinical deterioration in HIV tuberculosis (HIV-TB) co-infected individuals following initiation of antiretroviral therapy (ART). Here, we present a rare presentation of pTB-IRIS which manifested as a prostatic abscess in a case of HIV positive patient. To the best of our knowledge this is the first reported case of pTB-IRIS reported in literature which manifested as a prostatic abscess. Paradoxical TB-IRIS manifesting as prostatic abscess is extremely rare and a high index of clinical suspicion is needed to diagnose and appropriately treat it. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9498 Asian Journal of Medical Sciences 2014 Vol.5(4); 111-112